Modal analysis on dissimilar metal using different thickness (steel and aluminium) - Mohd Ridwan, Sulaiman (2012)
This project report deals with dynamic behaviour of joining between stainless steel and aluminium alloy by MIG welding using theoretical and experimental analysis method. This project report is to study the dynamic properties and behaviour of joining between stainless steel and aluminium alloy by MIG welding by using modal analysis and compare with the finite element analysis. The structural three-dimensional solid modelling of joining between stainless steel and aluminium alloy by welding was developed using the SOLIDWORK drawing software. The finite element analysis was then performed using ALGOR 23.1 (FEA). The finite element model of the components was analyzed using the linear modal analysis approach. Finally, the experimental modal analysis was performed using Impact Hammer Testing method. The natural frequency of the mode shape is determined and comparative study was done from both method results. The comparison between natural frequencies of finite element modelling and model testing shows the closeness of the results. From the results, the percentage error had been determined and the limitation in the natural frequency of the joining between stainless steel and aluminium alloy by welding is observed. The results of this project shown the mode shape of the joining plate by MIG welding for simulation are generally is not in agreement with the experimental value and the frequencies of the experimental modal analysis are a bit different with the frequencies of the simulation. The percentage error is bit high because there are some errors occur during the experimental modal analysis. The experimental modal analysis is conducted with fix condition of the joining plate between aluminium alloy and stainless steel by welding and the effect of damping which effect test rig by using polystyrene as a base of the plate is a factors as the higher percentage error. It is conclude that the in experimental method uses the polystyrene as a base affected the result.